Adsorption of Heavy Metals on Diatomite: Mechanism and Effect of Operating Variables - Jose Valente Flores-Cano; Roberto Leyva-Ramos; Erika Padilla-Ortega; Jovita Mendoza-Barron (Adsorption Science & Technology)
The adsorption capacity of diatomite towards heavy metals as well as the adsorption mechanism was investigated in the present study. The chemical and X-ray diffraction analyses revealed that the diatomite was mainly composed of SiO 2 (95.91%) as cristobalite and quartz. The maximum uptake of Cd(II), Zn(II), Pb(II) and Cr(III) were 0.734, 0.232, 0.169 and 0.162 meq/g at pH of 7, 6, 4 and 4, respectively. The adsorption capacity of diatomite was enhanced by increasing the temperature because the adsorption process was endothermic. The effect of the pH on the capacity was studied, and the maximum capacity augmented 6.3 times while increasing the pH from 4 to 7. This trend was due to the electrostatic interactions between the metal cations in solution and the negatively charged surface of the diatomite. The predominant adsorption mechanism of Cd(II) on diatomite was chemisorption, while ion exchange was responsible for 10% to 50% of the adsorption.